Kemampuan Pseudomonas putida Pf-20 dan 24.7B untuk Memperbaiki Sifat Kimia Media Tumbuh dan Ketahanan Terinduksi Tembakau H877 terhadap Cucumber mosaic virus - W. S. Wahyuni; A. Iwan; A. Mudjiharjati; T. C. Setyowati; H. Purwiko (Jurnal Perlindungan Tanaman Indonesia, 2005)
P. putida Pf-20 from medium M1 (paddy soil, leaves compost and manure compost, 1:3:2) has a higher affinity and more rapid to solubilize phosphate on Pikovskaya medium, rather than P. putida 27.4B. Those affinities of both strains from the media M1 with CMV-48 were much greater than that of medium without CMV. After 64 days planted, the content of N total, C-organic, CEC, K20, and P205 were better on medium M1, but the pH was little bit decreased. The reduction of P04 and Fe in medium M1 could due to the bacterial growth, and for producing siderophore, particularly on the media with viral treatment. These bacteria strains did not affect on the plant height and number of leaves on media M1, M2 or M3, however, these bacteria affected on the total root length and root densities in the medium M1 with virus. The more available nutrient in the medium, the more rapid bacteria colonized rhizosphere and roots. Both of these bacteria were effective to reduce the disease severity of CMV on tobacco H877. The medium M1 was the best medium for bacterial and tobacco growth.